Assessing different holding pen cooling systems through environmental variables and productivity of lactating cows - Silva, Danilo Corrêa; Passini, Roberta (Acta Scientiarum. Animal Sciences, 2017)
This studyaimed to assess different holding pen climatization systems for dairy cattle through environmental variables, milk production and economic indexes. Sixteen lactating cows were used, distributed in a 4 x 4 Latin square design consisting of four groups of four animals, assessed in four periods, seven days each, and in four holding pen environments: SUN– external environment (in the sun), SHA– 80%-protection polypropylenemesh shading, SHA + SPR– 80% polypropylene mesh shading + water sprinkling, SHA + SPR + VEN – 80% polypropylene mesh shading + water sprinkling + ventilation. The animals remained for 30 minutes in their respective environments. In this period, environmental variables were collected using data loggers, and the milk produced, in kg, by each animal was subjected to the treatments. Fixed and variable costs were calculated for economic analysis. The SHA + SPR + VEN treatment presented itself as the best environment (p < 0.05), promoting an increase in the milk produced by the cows and in themonthly income, with 44 days for return on investment.